FACTORS AFFECTING THE HUMAN DEVELOPMENT INDEX (HDI) IN CENTRAL JAVA PROVINCE - Muhammad Syariful Anam; Yuni Inawati; Rina Rosia (Riset Ekonomi Pembangunan, 2021)
This study examines the effects of poverty, gross regional domestic product (GRDP) and minimum wages on the human development index in Central Java Province. The data analysis method used in this research is panel data regression. From the results of selecting the best model, the regression model chosen is the fixed effect model. Based on the partial effect analysis results, it can be concluded conclude that poverty has a negative and significant effect on the human development index, while the GRDP and minimum wages have a positive and significant effect on the human development index. Then, poverty, GRDP and minimum wage simultaneously significantly affect the human development index in Central Java.